2014
DOI: 10.1002/ana.24020
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific control of central nervous system autoimmunity by p38 mitogen‐activated protein kinase signaling in myeloid cells

Abstract: Objective-Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system (CNS), characterized by a global increasing incidence driven by relapsingremitting disease in females. p38 MAP kinase (MAPK) has been described as a key regulator of inflammatory responses in autoimmunity, but its role in the sexual dimorphism in MS or MS models remains unexplored.Methods-Toward this end, we used experimental autoimmune encephalomyelitis (EAE), the principal animal model of MS, combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 68 publications
(162 reference statements)
8
52
0
Order By: Relevance
“…Augmented induction of T h 17 cells by high sodium has been shown to be dependent on a signaling pathway involving serum glucocorticoid kinase 1 and p38α MAPK in T cells, although the in vivo cell‐specific requirement for p38α for EAE exacerbation by dietary sodium has not been shown (4). Moreover, using cell type‐specific genetic ablation of p38α, we have previously shown that p38α plays cell‐specific roles in EAE independent of diet (24). Hence, we used the same approach to delineate the cell type‐specific contribution of p38 MAPK signaling to sodium‐mediated exacerbation of EAE.…”
Section: Resultsmentioning
confidence: 99%
“…Augmented induction of T h 17 cells by high sodium has been shown to be dependent on a signaling pathway involving serum glucocorticoid kinase 1 and p38α MAPK in T cells, although the in vivo cell‐specific requirement for p38α for EAE exacerbation by dietary sodium has not been shown (4). Moreover, using cell type‐specific genetic ablation of p38α, we have previously shown that p38α plays cell‐specific roles in EAE independent of diet (24). Hence, we used the same approach to delineate the cell type‐specific contribution of p38 MAPK signaling to sodium‐mediated exacerbation of EAE.…”
Section: Resultsmentioning
confidence: 99%
“…Data were normalized to the expression of the housekeeping gene, B2m. SYBR Green-based qRT-PCR was performed as described previously (65).…”
Section: Methodsmentioning
confidence: 99%
“…Downstream of cytokine activation, second messenger signaling and transcription factors also show sexspecific activity. For example, p38MAPK mediates symptoms only in females in a mouse model of multiple sclerosis (Krementsov et al, 2014), and lipocalin-2 is required for increasing body temperature after LPS in females but not males (Hamzic et al, 2013). Furthermore, COX-2 is required for hippocampal memory only in females (Guzm an et al, 2009).…”
Section: Neuroimmune Signaling and Plasticitymentioning
confidence: 99%
“…Male and female Sex not specified Lipton and Ticknor, 1979Uz et al, 2009† Moxley et al, 2002† Rantala et al, 2012† Ishido et al, 2015† Scotland et al, 2011Roberts et al, 2013Zheng et al, 2006 Bergh€ Lapchak et al, 1993Pugh et al, 1998* Balschun et al, 2003Pyter et al, 2013* Goshen et al, 2007Hudson et al, 2014Spulber et al, 2009Krementsov et al, 2014* Balschun et al, 2004Hamzic et al, 2013Braida et al, 2004 Guzm an et al, Hao et al, 2014Spencer-Segal et al, 2011Maher et al, 2005 Mizuno and Giese, 2012 Belarbi et al, 2013Harris et al, 2016Marciniak et al, 2015Polimanti et al, 2016† Rogers et al, 2011Czerniawski et al, 2015Czerniawski and Guzowski, 2014Guan and Fang, 2006Park et al, 2011Peters et al, 2010Chen et al, 2011Lee et al, 2015Steinmetz et al, 2016 immune signaling resulted in decreased BDNF and impaired differentiation of new cells into neurons. Here, BNDF levels and proliferation were rescued by wheel running despite persistent high levels of cytokines (Wu et al, 2007).…”
Section: Male Femalementioning
confidence: 99%